Advancing research on team process dynamics: Theoretical, methodological, and measurement considerations. (November 2015) - Kozlowski, Steve W. J.
Team processes are inherently dynamic phenomena theoretically, but they have largely been treated as static in research. It is well established that they are important contributors to team effectiveness; the lack of attention to dynamics means that team process mechanisms are essentially unstudied. I examine three primary themes. First, I speculate as to why it is that research treatments of team processes are largely static and what may account for this inertia. Second, I consider the conceptual underpinnings of process dynamics with respect to (a) emergence across levels and (b) in terms of variability, trajectory, and cyclical fluctuation. Third, I discuss three ways that research on team process dynamics can be advanced by: (a) adapting existing research methods, (b) creating innovative measurement techniques, and (c) advancing new research paradigms. Empirical examination of team dynamics is on the research frontier. These suggestions hold promise for advancing understanding of dynamic process mechanisms.